2003
DOI: 10.1159/000074037
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Levels Increase during Flutamide Therapy in Women with Polycystic Ovary Syndrome

Abstract: Aim: To evaluate the serum leptin levels and the effects of flutamide treatment on the leptin levels in women with polycystic ovary syndrome (PCOS). Methods: 20 women with PCOS and 20 controls were enrolled in the study. Leptin levels and leptin response to an oral glucose tolerance test were assessed in both groups before and after a 4-week flutamide therapy period. Results: The leptin levels were similar in both groups at baseline. In the PCOS group, leptin levels and area under curve for leptin levels incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…An inverse association of serum testosterone with circulating leptin in men has been reported previously in two studies of older adults 43,44 although the association was independent of obesity in only one 43 . Leptin levels in women with PCOS were positively related to the free androgen index in one study 45 and they were also found to be increased after androgen‐receptor blockade in another 46 which are in general agreement with the unadjusted regression results in this report.…”
Section: Discussionsupporting
confidence: 92%
“…An inverse association of serum testosterone with circulating leptin in men has been reported previously in two studies of older adults 43,44 although the association was independent of obesity in only one 43 . Leptin levels in women with PCOS were positively related to the free androgen index in one study 45 and they were also found to be increased after androgen‐receptor blockade in another 46 which are in general agreement with the unadjusted regression results in this report.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, in agreement with the current literature, it is shown that LH, LH/FSH ratio and androgen levels are elevated and SHBG levels are lowered in both obese and lean subjects with PCOS compared with obese controls 26,30,32,36–38 . This finding, together with the observation that these parameters were similar in LeanPCOS and ObPCOS groups suggest that there should be certain mechanisms that lead tohyperandrogenism, elevated LH/FSH ratio and lowered SHBG in PCOS subjects other than obesity per se .…”
Section: Discussionsupporting
confidence: 92%
“…Leptin and ghrelin in contraceptive use. Fertil Steril 2009. levels increased with EE and cyproteroneacetate or flutamide as antiandrogenic therapy in women with PCOS(48,49).…”
mentioning
confidence: 93%